Adaptasi Masyarakat Terkait Pencemaran Air Di Tempat Pembuangan Akhir (TPA) Sampah Ciangir Kecamatan Tamansari Kota Tasikmalaya - Ega Saputra; Muhammad Rizky Fauzan; Raisul Muslim; Indra Gunawan; Resti Pebrianti; Yani Sri Astuti (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research discusses community adaptation to water pollution around the Ciangir Waste Final Disposal Site (TPA), Tamansari District, Tasikmalaya City. The research method used is descriptive qualitative with a focus on community adaptation to water pollution. The research results show that the community around the Ciangir landfill has shown passive adaptation to the environmental pollution conditions that occur around them. Even though the quality of well water is affected by water pollution from the landfill, residents do not consume water from the landfill because they have access to clean wells. Water from the landfill is used only for agricultural irrigation purposes after going through a certain processing process. Apart from that, the research also found that licit water from the landfill was not significantly affected during heavy rain, but the river water around the landfill became cloudy due to the flow of rainwater which carried polluting particles. Residents around the Ciangir TPA only use water from the TPA for agricultural irrigation purposes, while for daily consumption needs, they prefer to use water from the clean wells they own. The local government does not pay adequate attention to waste management at the Ciangir landfill, which has the potential to increase the negative impact of water pollution around the landfill. The suggestion proposed is that the government immediately take steps to move the piles of rubbish to safer and more suitable empty land to reduce the impact of water pollution caused by the Ciangir landfill. In dealing with water pollution conditions around the Ciangir Waste Landfill, the community has adapted by using water from the landfill for agricultural irrigation.